Investigating the influence of selenium and epibrassinolide on antioxidant activity, proline accumulation, and protein expression profiles in wheat plants experiencing heat and drought stress - Khan, Tanveer Alam; Ahmad, Aqeel; Saeed, Taiba; Yusuf, Mohammad; Faisal, Mohammad; Alatar, Abdulrahman Alatar (Frontiers in Plant Science, 2024)
In the current investigation, the combination of selenium (Se) and epibrassinolide (EBL) exhibited a promising alleviative response against the concurrent stress of heat and drought in wheat plants.The compromised growth and photosynthetic performance of wheat plants under the combined stress of heat and drought substantially improved with the treatment involving Se and EBL. This improvement was facilitated through the expression of Q9FIE3 and O04939 proteins, along with enhanced antioxidant activities. The heightened levels of antioxidant enzymes and the accumulation of osmoprotectant proline helped mitigate the overaccumulation of reactive oxygen species (ROS), including electrolyte leakage, H2O2 accumulation, and lipid peroxidation, thus conferring tolerance against the combined stress of heat and drought. Studies have demonstrated that Se and EBL can assist wheat plants in recuperating from the adverse effects of heat and drought. As such, they are essential components of sustainable farming methods that aim to increase crop productivity.